Research Progress in Cathode Catalysts for Li-CO2 Batteries - He, Kai (MATEC web of conferences, 2023)
The need for environmentally friendly and effective energy storage technologies is growing urgently in response to the rising energy demand and the seriousness of the environmental issues, in order to meet the Double Carbon objective. Li-CO2 batteries are a newer battery technology that has drawn a lot of interest. Its distinctiveness comes from the utilization of CO2 as a key component in energy storage, which can efficiently transform CO2 supplies into energy preservation and potentially be sustainable and environmentally friendly. This article examines the Li-CO2 battery's internal working mechanisms, delves into the selection and development of positive electrode catalysts, and contrasts several materials to list their benefits and drawbacks. Carbon-based materials, precious metals, and their compounds, and transition metals and their complexes are the main areas of emphasis. Carbon materials' exceptional conductivity, enormous specific surface area, and high commercial viability are underlined. The performances of precious metals and transition metals paired with carbon materials are compared in detail. Finally, suggestions for further research into potential cathode catalytic materials for Li-CO2 batteries are provided based on the effectiveness and practical utility of various materials. In an attempt to combat global warming and environmental pollution, new methods for converting waste gases, such as carbon dioxide, into energy will be developed thanks to research on Li-CO2 batteries. The features of this battery technology, such as its high density of energy and lengthy cycle life, are projected to make it more practical to store and use renewable energy.